Improvement of traditional poultry housing production capacity using feather tool In Sapuran District, Wonosobo District - Dini Cahyandari; M Toni Prasetyo (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2019)
Chicken Slaughtering Business Ms. Siti has been pioneering this business since the early 1990s and still survives until now. In her efforts Ms. Siti bought broilers from chicken farmers around the neighborhood. Then it is processed to continue to be sold to traditional markets in Sapuran District. Whereas Mrs. Mundri's chicken slaughtering business began around the beginning of the 2000s. Every day around 100 chickens are processed to be marketed later. Which is one of the problems for Chicken Slaughter Business including IbM Partner Industry The slaughtering business of Ms. Siti's chicken is the sanitation of the chicken slaughtering process until the marketing process. Chicken slaughterhouse is less hygienic, so that in this IbM service activity the implementer will introduce a more hygienic chicken processing process. Activities another problem is the use of human energy in the process of turning chicken feathers which results in high production costs and a large degree of dependence on human labor. Another problem is processing chicken into processed products that have higher economic value and are more durable.